A novel facile one-pot synthesis of photothermally responsive carbon polymer dots as promising drug nanocarriers. Issue 19 (12th January 2022) - Consoli, Grazia Maria Letizia; Giuffrida, Maria Laura; Satriano, Cristina; Musumeci, Teresa; Forte, Giuseppe; Petralia, Salvatore
Abstract : A luminescent and photothermic carbon-based nanomaterial composed of a carbonized polymer core and polymer cross-linked chains: a promising nanocarrier for effective thermo-/photo-induced drug release activity. Abstract : Luminescent and photothermic carbon polymer dots (CPDs–PNM), composed of a carbonized core and cross-linked chains of poly( N -isopropylacrylamide), were synthetized by a novel, simple, solvent- and reagent-free method. The formation of CPDs–PNM was controlled by both temperature and heating time. The CPDs–PNM exhibited LCST behaviour, high photothermal conversion efficiency, curcumin loading capacity and no toxicity to eukaryotic cells. Proof of concept experiments confirmed an excellent thermally induced drug release activity to be used for photothermally controlled drug release.